Cultura participativa: - SAMPAIO, Victória Feitosa. (2024)
It is known that in Tocantins there is a lack of experiences of what we call pop culture, which are events, conventions and meetings aimed at the geek universe. The state's Jedi Council was the great impeller that introduced Star Wars fans, and science fiction fans in general, to new ways of relating to one another. The internet played an essential role for this way of living a love in the state for Star Wars to materialize and reinvent. The research deals directly with the existing relations between identity and media culture, in addition, there is little scientific production that encompasses the cultural relationship of fans, especially if we delimit to female fans in the state of Tocantins. The theoretical framework is based on the authors Jenkins, Hall, Lévy, Saquet and Shirky. This problematization is very relevant, it is necessary to understand how women occupy these spaces, if they are event organizers or mere supporting actors, if they cosplay and if, because of that, they suffer harassment, how their families see them, if they suffer discrimination and criticism, if they feel if they are inferior when they are with other male fans, if they share the dedication to conventions and meetings with housework and if they are mothers, for example. In order to combat any discrimination based on gender and to promote an egalitarian space, it is necessary to study its agents and their behavior. In order to do so, we intend to carry out interviews with these women from Tocantins, mainly residing in Palmas and Araguaína, so that we can reach the answers to the problematizing questions.